Loyalitas Wisatawan pada Layanan Fastboat PT. Caspla Bali di Pelabuhan Sanur - I Putu Aditya Pramana; Ni Kadek Winda Yanti (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study aims to examine the effects of service quality, consumer experience, perceived security, and service satisfaction on tourist loyalty. The sample consisted of 170 respondents. Data analysis techniques included validity testing, reliability testing, classical assumption tests, multiple linear regression analysis, the coefficient of determination, the F-test, and the t-test. The results indicate that service quality has a positive and significant effect on tourist loyalty; consumer experience has a positive and significant effect on tourist loyalty; perceived security has a positive and significant effect on tourist loyalty; and service satisfaction has a significant effect on tourist loyalty. Based on these findings, it is recommended that the management of PT Caspla Bali at Sanur Harbor enhance staff competence and knowledge in serving tourists by providing regular training, consistently delivering services that meet or exceed promises made to tourists, and ensuring the availability of complete and modern safety equipment to increase tourist trust. Furthermore, continuous efforts should be made to improve service quality, consumer experience, perceived security, and service satisfaction in order to strengthen tourist loyalty.